TINDAK TUTUR DIREKTIF DALAM FILM UNTUK ANGELINE KARYA JITO BANYU - Jayanti, Fitri; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCommon problems are limited to three subproblems related to (1) the type of speech act directive which consists of asking, asking, ordering, prohibiting, allowing, advising, (2) how the context is, (3) implementation in school. The purpose of the study is to describe the type of speech acts, describe the context, and implementation plan in school. The method used in this research is descriptive method with qualitative research form. Sources of data and data in this research is the film For Angeline by Jito Banyu, and the data in the form of speech directive. The technique used in this research is a documentary study technique, while the data collection tool is the researcher himself as a key instrument. Keywords: speech act, directive, film, for angeline.